Experimental methodology for obtaining sound absorption coefficients - Carlos A. Macía M; Hernán D. Sepúlveda D (Universidad de Antioquia, 2011)
Objective: the authors propose a new methodology for estimating sound absorption coefficients using genetic algorithms. Methodology: sound waves are generated and conducted along a rectangular silencer. The waves are then attenuated by the absorbing material covering the silencer's walls. The attenuated sound pressure level is used in a genetic algorithm-based search to find the parameters of the proposed attenuation expressions that include geometric factors, the wavelength and the absorption coefficient. Results: a variety of adjusted mathematical models were found that make it possible to estimate the absorption coefficients based on the characteristics of a rectangular silencer used for measuring the attenuation of the noise that passes through it. Conclusions: this methodology makes it possible to obtain the absorption coefficients of new materials in a cheap and simple manner. Although these coefficients might be slightly different from those obtained through other methodologies, they provide solutions within the engineering accuracy ranges that are used for designing noise control systems.